The Influence of Knowledge, Attitude, and Facility Availability on Solid Medical Waste Disposal with Compliance as an Intervening Variable at RSU PKU Muhammadiyah Delanggu Hospital - Astuti, Dian Juli; Imronudin, I; Iza, Muzakar (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze the influence of knowledge, attitude, and facility availability on solid medical waste disposal, with compliance as an intervening variable at RSU PKU Muhammadiyah Delanggu HospitalMethodology: The research employed a quantitative explanatory approach using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to 80 healthcare workers selected using purposive sampling techniques Results: The results revealed that knowledge, attitude, and facility availability have a positive and significant effect on compliance, and compliance significantly influences solid medical waste disposal practices. Moreover, compliance was found to be a strong mediating variable linking the three independent variables to waste disposal behavior. Applications/Originality/Value: These findings indicate that proper medical waste management behavior depends not only on individual factors but also on adequate system and facility support. The study concludes that improving knowledge, fostering positive attitudes, and providing sufficient facilities can enhance compliance and improve the effectiveness of solid medical waste management in hospitals.